2006
DOI: 10.1182/blood-2006-04-018556
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of C2GnT-I glycosyltransferase renders T lymphoma cells resistant to cell death

Abstract: Neoplastic T cells in mycosis fungoides (MF)are resistant to apoptotic agents, including galectin-1 that is abundant in skin. Although MF cells are typically CD7 ؊ , and thus galectin-1 resistant, CD7 ؉ HH cells, derived from a patient with MF, were also resistant to galectin-1. HH cells demonstrate altered cell surface glycosylation, with loss of core 2 Oglycan ligands for galectin-1 created by core 2 ␤1,6-N-acetylglucosaminyltransferase (C2GnT-I). Loss of core 2 O-glycans on tumor cells was also seen in prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 57 publications
1
39
1
Order By: Relevance
“…1B). However, in contrast to what we have observed for galectin-1 T cell death (9,10,40), expression of the core 2 ␤-1,6-N-acetylglucosaminyltransferase (C2GnT) was not essential for galectin-9-induced death, as BW5147 T cells that lack C2GnT expression were susceptible to galectin-9-induced cell death, whereas the cells were resistant to galectin-1 (Fig. 1B).…”
Section: Galectin-9-induced T Cell Death Requires Different Glycan LIcontrasting
confidence: 50%
See 1 more Smart Citation
“…1B). However, in contrast to what we have observed for galectin-1 T cell death (9,10,40), expression of the core 2 ␤-1,6-N-acetylglucosaminyltransferase (C2GnT) was not essential for galectin-9-induced death, as BW5147 T cells that lack C2GnT expression were susceptible to galectin-9-induced cell death, whereas the cells were resistant to galectin-1 (Fig. 1B).…”
Section: Galectin-9-induced T Cell Death Requires Different Glycan LIcontrasting
confidence: 50%
“…1B). We also examined the human HH T cell line, which, like BW5147 cells, has reduced cell surface core 2 O-glycans and is resistant to galectin-1 (40), and found that HH cells were also susceptible to galectin-9 (data not shown). Thus, unlike galectin-1, galectin-9-induced cell death does not require expression of core 2 O-glycans on cell surface glycoprotein receptors.…”
Section: Galectin-9-induced T Cell Death Requires Different Glycan LImentioning
confidence: 99%
“…We have also recently determined that malignant T cells from some patients with cutaneous T-cell lymphoma have aberrant cell-surface glycosylation and are thus resistant to galectin-1-induced cell death (8). Specifically, we identified malignant T cells from one patient with a single point mutation in core 2 GnT that abrogated enzyme activity and conferred galectin-1 resistance (46). We found that core 2 GnT is highly expressed in parental PSA + LNCaP cells that are susceptible to galectin-1-induced death and markedly reduced in PSA À LNCaP cells that produce abundant galectin-1 and are resistant to galectin-1-induced cell death.…”
Section: Discussionmentioning
confidence: 97%
“…Gal1 induces apoptosis of activated CD8 T cells (18) and induces Th2 cytokine shifts. Expression of C2GnT (core 2 ␤-1,6-N-acetylglucosaminyltransferase) by T cells, which initiates a second branch on O-glycans, later elongated with poly-N-acetyllactosamine moieties, renders activated T cells susceptible to gal1-induced apoptosis (19,20). Differential glycosylation of Th1, Th2, and Th17 CD4 T cells results in differential sensitivity to gal1-induced apoptosis.…”
mentioning
confidence: 99%
“…On O-glycans, the lectin peanut agglutinin (PNA) recognizes asialo core 1 O-glycans, the substrate on which the enzyme C2GnT adds the second branch of core 2 O-glycans (19,20), later elongated with poly-N-acetyllactosamine moieties, to which gal1 binds. The dTs bound significantly more PNA than the pTs ( Fig.…”
mentioning
confidence: 99%